THE EFFECT OF GIVING DRAGON FRUIT JUICE ON INCREASING HEMOGLOBIN LEVELS IN ADOLESCENT GIRLS EXPERIENCED WITH ANEMIA AT THE RIYADHUL MUBTADI'IEN ISLAMIC BOARDING SCHOOL, PESAWARAN DISTRICT - Nur Azizah, Lutvi; desni sagita, Yona Desni Sagita; sanjaya, Riona Sanjaya; maulia, Maulia Isnaini (Universitas Aisyah Pringsewu, 2024)
The prevalence of anemia among female adolescents in Lampung Province is 24.8 percent, according to 2018 Riskesdas data. Dragon fruit consumption is one non-pharmacological strategy that can be used to lower the prevalence of anemia in teenagers. The research objective was to determine how giving dragon fruit juice increases hemoglobin levels in adolescent girls with anemia at the Riyadhul Mubtadi'ien Islamic Boarding School of Pesawaran Regency. The type of research used is quantitative, with a pre-experiment research design with a one group pretest-posttest design approach. This research was conducted at the Riyadhul Mubtadi'ien Islamic Boarding School of Pesawaran Regency in May-June 2024. The population in this study was 34 young women and 32 samples of young women using accidental sampling technique. Bivariate analysis used is using Wilcoxon. The results of the bivariate analysis showed that the P value = 0.000 <= 0.05, which shows the effect of giving dragon fruit juice on increasing hemoglobin levels in adolescent girls with anemia.